2005
DOI: 10.1620/tjem.207.223
|View full text |Cite
|
Sign up to set email alerts
|

Mood Scores in Relation to Hormone Replacement Therapies during Menopause: A Prospective Randomized Trial

Abstract: There is lack of studies in literature about the long-term effects of hormone replacement therapies and cholesterol levels on mood scores in menopause. In the present study we have investigated whether serum lipid levels affect mood scores in menopause and evaluated the long-term effects of the combined hormone replacement regimens (HRT) on depressive symptoms in postmenopausal women. In this prospective-randomized, placebo-controlled, double-blind study, 286 women in menopause were divided into four groups ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…For example, it is possible that estrogen may protect women from inflammatory processes during depressive episodes. In line with this, hormone replacement therapy has had positive long-term effects on mood of menopausal women (41,42).…”
Section: Discussionmentioning
confidence: 82%
“…For example, it is possible that estrogen may protect women from inflammatory processes during depressive episodes. In line with this, hormone replacement therapy has had positive long-term effects on mood of menopausal women (41,42).…”
Section: Discussionmentioning
confidence: 82%
“…1) Three noninterventional survey studies showed either no effect of MHT on mood symptoms or effect only in white women with menopausal symptoms (317-319). 2) Two RCTs showed improvement in mood symptoms in postmenopausal women with mild to moderate depression, albeit with unblinded assignment to and lack of baseline depression matching for the active placebo group (320,321).…”
Section: Rctsmentioning
confidence: 99%
“…In peri-and postmenopausal women, oestrogen therapy has mood-modulating effects, as it increases feelings of well-being and decreases depression scores. 13,14 Similarly, in transwomen, oestrogen therapy produces a positive effect on mood. 15,16 Anecdotally, many patients report an increased feeling of femininity on oestrogen therapy and a calmer mood in reaction to a reduction in their feelings of being male.…”
Section: Physical Effectsmentioning
confidence: 99%